THE ROLE OF LISTERIA IN INFECTIOUS PATHOLOGY OF ANIMALS AND HUMANS - G.U.Sagdullaeva; M.Mustafayeva (Лучшие интеллектуальные исследования, 2024)
Abstract: A modern concept of the development of cells of infectious forms in animals and humans is presented. An analysis of the main factors determining the rapid increase in the incidence of listeriosis in recent years was carried out: infection and active reproduction of listeria in food products, increased sensitivity to listeria in the risk group against the background of the level of cellular immunity. The features of intracellular parasitism and the expression of Listeria pathogenicity factors are considered. Analysis of various methodological approaches to the diagnosis of listeriosis indicates the leading role of bacteriological methods for the isolation and identification of L.monocytogenes based on modern selective agents and the need for their development in modern medical laboratories and sanitary surveillance centers.